Theological Exegesis and Aquinas's Treatise ‘against the Greeks’ - Jordan, Mark D. (Church history, 1987)
According to Pope Leo XIII, it could almost be said that Thomas Aquinas “presided” over the deliberations at Lyons (1274) and Florence (1438) when these councils confronted the Greek church.1 This judgment, which would be true at best and in part only for the later council, both enshrines and encourages a misreading of Thomas's short treatise Contra errores Graecorum. In fact, the Contra errores is neither as well informed nor as technically argued as other Latin polemics of the twelfth and thirteenth centuries. It is a treatise limited in form and argument, motivated by another, poorer treatise.